Incidence, Degree, and Development of Graft Hypertrophy 24 Months After Matrix-Induced Autologous Chondrocyte Implantation: Association With Clinical Outcomes. (September 2015) - Ebert, Jay R.; Smith, Anne; Fallon, Michael; Butler, Rodney; Nairn, Robert; Breidahl, William; Wood, David J.
Background: Graft hypertrophy is a common occurrence after periosteal, collagen-covered and matrix-induced autologous chondrocyte implantation (MACI). Purpose/Hypothesis: The purpose of this study was to investigate the incidence, development, and degree of graft hypertrophy at 24 months after MACI. The hypothesis was that graft hypertrophy would not be associated with clinical outcome at 24 months. Study Design: Case series, Level of evidence, 4. Methods: This study was undertaken in 180 consecutive patients (113 male, 67 female) after MACI in the knee. All patients were assessed clinically using the Knee injury and Osteoarthritis Outcome Score (KOOS) and underwent magnetic resonance imaging (MRI) at 3, 12, and 24 months after surgery. The incidence of hypertrophy relevant to anatomic graft site was investigated, as was the progressive change in hypertrophic studies postoperatively. The degree of tissue overgrowth in hypertrophic cases was investigated, as was its association with patient clinical outcome at 24 months after surgery. Results: Of the 180 patients, 50 demonstrated a hypertrophic graft at 1 or more postoperative time points. This included 9 grafts (5.0%) at 3 months and 32 grafts (18.7%) at 12 months. At 24 months, 47 grafts (26.1%)—43 (32.1%) tibiofemoral and 4 (8.7%) patellofemoral—were hypertrophic. Patients with hypertrophic grafts at 24 months (n = 47) were younger ( P = .051), they had a lower body mass index (BMI; P = .069), and significantly fewer of them had patellofemoral grafts ( P = .007) compared with patients who had grafts with full (100%) tissue infill (n = 61). There were no significant differences in any of the KOOS subscales between patients with graft hypertrophy or full (100%) tissue infill at 24 months after surgery, while the severity of graft hypertrophy was not associated with KOOS subscales at 24 months. Conclusion: Hypertrophic grafts after MACI were common and continued to develop through to 24 months after surgery. Hypertrophic growth was associated with being younger and having a lower BMI, was more common on the femoral condyles, and overall was not associated with clinical outcome at 24 months after surgery. However, further research with longer term follow-up is required to evaluate the effect of persistent hypertrophy on graft stability and to assess the use of early surgical intervention to prevent such failure.